2023
DOI: 10.3390/antiox12030774
|View full text |Cite
|
Sign up to set email alerts
|

Hangover-Relieving Effect of Ginseng Berry Kombucha Fermented by Saccharomyces cerevisiae and Gluconobacter oxydans in Ethanol-Treated Cells and Mice Model

Abstract: This study aimed to evaluate the hangover relieving effect of ginseng berry kombucha (GBK) fermented with Saccharomyces cerevisiae and Gluconobacter oxydans in in vitro and in vivo models. The antioxidant activity and oxidative stress inhibitory effect of GBK were evaluated in ethanol-treated human liver HepG2 cells. In addition, biochemical and behavioral analyses of ethanol treated male ICR mice were performed to confirm the anti-hangover effect of GBK. The radical scavenging activity of GBK was increased by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In vivo assay -n = 50 (5 groups with 10 Galleria mellonella larvae); -Toxicity assays. [58] To evaluate the hangover relieving effect of ginseng berry Kombucha (GBK) fermented with Saccharomyces cerevisiae and Gluconobacter oxydans in in vitro and in vivo models.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo assay -n = 50 (5 groups with 10 Galleria mellonella larvae); -Toxicity assays. [58] To evaluate the hangover relieving effect of ginseng berry Kombucha (GBK) fermented with Saccharomyces cerevisiae and Gluconobacter oxydans in in vitro and in vivo models.…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear factor erythroid 2‐related factor 2 (NRF2) is an essential transcription factor in the antioxidant defense, and its activation by ROS generated during alcohol metabolism can alleviate ALD 41 . It was reported that an increased gene or protein expression of NRF2 could lessen alcohol induced damage in liver cells 21 and liver tissues of mice 42 . Under oxidative stress conditions, NRF2 binds to antioxidant responsive elements in nuclei and then promotes the downstream gene expressions of antioxidant enzymes, that is, heme oxygenase‐1 (HO‐1), NAD(P)H quinone oxidoreductase 1 (NQO1), SOD, CAT, GPx, etc 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, during alcohol metabolism, the large production of reactive oxygen species (ROS) and imbalanced energy metabolism resulted in hepatosteatosis or even hepatitis. Previous reports indicated that some natural agents could ameliorate liver damage against chronic alcohol consumption via antioxidation, anti‐inflammation, or upregulation of fatty‐acid β oxidation in livers, that is, Antrodia camphorata , 16 Aloe vera polysaccharide, 17 wheat embryo, 18 Lactobacillus spp., 19 olive oil, 20 and ginseng berry kombucha 21 . Hence, a strategic development of hepatoprotective agents from natural food sources against an alcoholic liver disease (ALD) rather than medical therapy warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of Nrf2 is typically inhibited by its negative regulator Keap1, but can detach from Keap1 and move into the nucleus during oxidative stress conditions (Jayasuriya et al, 2021). Activation of the Nrf2-Keap1 signaling pathway is a well-established method for reducing oxidative stress-induced liver damage (Choi et al, 2023). Furthermore, in stressful environments, the Nrf2-Keap1 pathway can bind to antioxidant response elements and activate downstream genes like HO-1, GCLC, and GPX-1.…”
Section: The Xztz Eases Hepatic Inflammatory Response Via Mapks/nf-kb...mentioning
confidence: 99%